"Na sala de justiça" : o divórcio e as modalidades de regulação jurídica da família no Brasil - Neris, Cidinalva Silva Câmara (2015)
This research is situated in the field of studies on political and legal regulation ways of family relationships, and aims to analyze the new modalities of legal treatment to the divorce in contemporary Brazil. The social and political determinants applied to the family sphere in the context of everyday juridical regulation of the breakdown of marital relationships modes are investigated. The empirical framework is based on four family juridical circuits at the Court of São Luís, Maranhão state capital. The study then focused on the apprehension of the assumptions and implications adopting the principle of facilitation of marital dissolution as juridical reaction model to the interpersonal conflict. Thus, it is focused a variety of aspects that precede and condition the juridical treatment of divorce, and the effects of the required meeting between judges and those who is getting the divorce in a legal framework of interaction aiming to regulate the particular conflicts. Moreover, were mobilized different methodological devices such as sociographic analysis of legal process, archival research, interviews with the actors involved (people in the process of getting a divorce, judges, justice officials) and ethnographic observation at the Court hearing. Based on this study, it was found that the juridical treatment of divorce reveals the ambiguities of institutional logic of public management of private domain, and the state of relations between the spouse and their representations of themselves, about family, marriage and the justice.